2022
DOI: 10.3390/healthcare10030531
|View full text |Cite
|
Sign up to set email alerts
|

Low-Pressure Laparoscopy Using the AirSeal System versus Standard Insufflation in Early-Stage Endometrial Cancer: A Multicenter, Retrospective Study (ARIEL Study)

Abstract: The aim of our study was to evaluate the benefits of a low-pressure insufflation system (AirSeal) vs. a standard insufflation system in terms of anesthesiologists’ parameters and postoperative pain in patients undergoing laparoscopic surgery for early-stage endometrial cancer. This retrospective study involved five tertiary centers and included 152 patients with apparent early-stage disease who underwent laparoscopic surgical staging with either the low-pressure AirSeal system (8–10 mmHg, n = 84) or standard l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…This capability enables surgery at low pressures that are unachievable with conventional insufflators. [ 15 ] There are few studies in the literature examining the effects of different pressures on outcomes in RARP surgeries.…”
Section: Discussionmentioning
confidence: 99%
“…This capability enables surgery at low pressures that are unachievable with conventional insufflators. [ 15 ] There are few studies in the literature examining the effects of different pressures on outcomes in RARP surgeries.…”
Section: Discussionmentioning
confidence: 99%
“…The stretching of CO 2 gas can irritate the diaphragm, causing shoulder pain. 13 Many previous trials have found that there are many ways to reduce the occurrence of shoulder pain after laparoscopic surgery, such as perioperative use of anesthetics, 14,15 pulmonary recruitment maneuver, 8,16 intraoperative use of low pneumoperitoneal pressure, 17,18 and postoperative intraperitoneal drainage. 1,9 These interventions did not stratify the population and this may result in patients who would not experience shoulder pain being exposed to these interventions without benefit or even with possible harm.…”
Section: Discussionmentioning
confidence: 99%
“…The AirSeal system reportedly helps to reduce shoulder pain due to excessive intraperitoneal pressure during laparoscopic surgery compared with the conventional insu ator, which has a mechanical valve on the access port (2)(3)(4). Moreover, this system shortens the operative time because it constantly maintains a large intra-abdominal space for surgical procedures (5).…”
Section: Introductionmentioning
confidence: 99%